The role of AtNUDT7, a Nudix hydrolase, in the plant defense response - Ge, Xiaochun (Landes Bioscience, 2008)
Nudix hydrolases constitute a large family of proteins that hydrolyze nucleoside diphosphate derivatives. Some Nudix hydrolases act as ‘housecleaning’ enzymes whereas others may function to sense and modulate the levels of their substrates to maintain physiological homeostasis. The Arabidopsis genome encodes 32 Nudix proteins (AtNUDTs). However, their physiological substrates and biological functions are little known. AtNUDT7 has been identified as a negative regulator of the defense response and its loss-of-function mutation leads to enhanced disease resistance and makes the plants hyper-responsive to inciting agents including pathogenic as well as nonpathogenic micro-organisms. Based on in vitro enzymatic characterization, it was speculated that ADP-ribose (ADPR) and/or NADH may be biologically significant substrates of AtNUDT7. However, our result from determination of the levels of ADPR and NAD(H) in the mutant and wild-type plants indicates neither of these nucleotide analogs likely is its physiological substrates. The Atnudt7 mutant does have a higher ratio of GSSG/GSH than wild-type plants. This alteration in redox homeostasis may prime the mutant plants for excessive cellular stimulation when being provoked by biotic stresses.